Music and Guided Imagery-Based Interventions for Psychological Outcomes in Breast Cancer Patients: A Systematic Review - Darmawan, Luh Gede Wirani Riskayanti; Sukartini, Tintin; Suarilah, Ira (Jurnal Berita Ilmu Keperawatan, 2026)
Psychological stress, such as anxiety and depression, is commonly experienced by women battling breast cancer, and this can significantly interfere with treatment adherence and recovery. Mind-body therapies such as music therapy and guided visualization are increasingly being used to help, although their effectiveness can vary from person to person. This systematic review aims to examine the benefits of these therapies for breast cancer patients. We searched four major databases—PubMed, Scopus, ScienceDirect, and Wiley Library—for randomized controlled trials from 2015 to 2025. We looked for studies in adult patients using these methods, with anxiety and depression as the primary outcomes measured, and things like stress, quality of life, and overall well-being as additional outcomes. We assessed bias using RoB 2.0 and mapped it with ROBVIS. The entire process followed PRISMA guidelines and was registered in PROSPERO under number CRD420251021032. Due to the high variability in study results, we opted for a narrative summary rather than detailed data analysis. Ultimately, we collected 12 studies covering breast cancer patients in stages 1 to 4. Sessions lasted between 12 and 60 minutes, spread over one to six weeks, and most included several relaxation techniques. Overall, people experienced a steady decrease in anxiety, depression, stress, and other mental pressures, along with better ways to manage emotions and an improved quality of life. It appears that music therapy and guided visualization can indeed make a difference in improving psychological well-being for women with breast cancer. However, it is important to note that these results should be considered carefully due to the uniqueness of the studies and the variation in outcomes. Therefore, moving forward, we need more robust randomized trials with clear intervention methods and standardized outcome tracking to build a stronger case.